Effect of dissolved organic matter on selective oxidation of toluene by ozone micro-nano bubble water. (June 2023) - Xie, Zeming; Shentu, Jiali; Long, Yuyang; Lu, Li; Shen, Dongsheng; Qi, Shengqi
Abstract: The oxidation capacity of ozone micro-nano bubble water (OMBW) was always higher than ozonated water due to enhanced contact by bubble interface, while the effect of coexisted dissolved organic matter (DOM) on the oxidation efficiency was still unclear. In this paper, batch experiments were carried out to investigate the selective oxidation of toluene by both OMBW and ozonated water (OW) with coexisted DOM in water. Five types of background solutions were applied in this study, including humic acid solution, fulvic acid solution and three types of diluted landfill leachates at the same content of total organic carbon. Results showed that coexisted DOM had a greater inhibition effect on toluene oxidation rate by OMBW, and the oxidation rate of toluene by OMBW and OW became close. It was mainly caused by the decreased reaction rate between toluene and hydroxyl radical ( k T -OH· ) in OMBW after the introduction of DOM, which competed for the adsorption sites on micro-nano bubble interface. The fraction of ozone to oxidize toluene as well as k T-OH· was in positive correlations with SUVA254 and the content of humic acid-like substances, but negatively correlated with E2 /E3, content of tryptophan-like proteins and content of fulvic acid-like substances. In addition, increasing the ozone dose was not effective in increasing the utilization rate of ozone in OMBW due to limited adsorption sites on micro-nano bubble interface. The paper was conductive to the application of ozone micro-nano bubble water in groundwater remediation with complex water matrices. Graphical abstract: Image 1 Highlights: The effect of DOM on toluene oxidation rate by OW and OMBW was investigated. DOM competed for adsorption sites on micro-nano bubble surface and reduced k T-OH· . Fulvic acid had a greater inhibition effect on toluene oxidation than humic acid. Increasing ozone dose did not improve its ratio in oxidizing toluene for OMBW.